Mulheres em cadeira de rodas e a relação com a deficiência adquirida: problemas, superações e possibilidades - Figaro, Fernanda Bertasso (2022)
Questions about disability, accessibility and violence permeate the routine of people who have some physical, intellectual and/or sensory limitation. This research proposed to understand the experiences of women in wheelchairs with acquired physical disabilities and the use of the wheelchair, identifying how adaptations occur, the difficulties faced after acquiring this new condition and raising the coping strategies, attitudes and obstacles in this situation. The research was of an exploratory quantitative and qualitative character. Data collection was performed by applying the World Health Disability Assessment Schedule – WHODAS 2.0 instrument and through a semi-structured interview analyzed by Content Analysis (Bardin, 1977). The participants were 10 women, aged between 35 and 65 years old, with acquired physical disabilities who use a wheelchair. From the results achieved, it was identified that the disability was acquired by accidents, violence and diseases. The data showed that the participants have functional impairment and found strategies to overcome limitations and disabilities expressed by people that are incompatible with physical disability and the use of a wheelchair. In this context, they developed strategies to overcome limits, both clarifying and affirming to others that they are not disabled, and also as they managed to understand that the stigmas they receive come from little or no information about disabilities. As for the use of a wheelchair, this assistive technology enables women's autonomy and independence, in addition to redefining their self-image. It is concluded that it is relevant and necessary for society to understand that people with disabilities have full and effective social participation on an equal basis with other people, respecting freedom, citizenship rights and providing adaptations and resources for the quality of life of this public; and that some women sought psychological care after acquiring the disability and using a wheelchair(AU)